PENDAPATAN DAN TINGKAT KESEJAHTERAAN RUMAH TANGGA PETANI UBI KAYU DI KABUPATEN LAMPUNG SELATAN - Grace Lia Ronauli Siahaan; Teguh Endaryanto; Muhammad Ibnu (Lampung University, 2021)
This reseach aims to analyze the condition of cassava agribusiness, household income, and level of household welfare of cassava farmers in South Lampung District. This research is a survey research involving 50 cassava farmers who were selected randomly. Data collection was carried out in May - June 2018. The data analysis method used was a qualitative descriptive approach to determine the condition of the agribusiness system and describe the level of household welfare of cassava farmers and a quantitative descriptive approach to determine the amount of household income of cassava farmers. The study shows that the conditions of the agribusiness system has not been well in several subsystems. The average income of cassava farming is IDR29,458,390.00 per year on land area of 0.65 hectares. Cassava farming contributes 62.34% of family income. Using BPS 2014 and Sajogyo (1997) standards, cassava farmers are considered living well.Key words: cassava farming, household, income